PERANAN AGAMA DALAM MEMBENTUK IDENTITAS DAN BUDAYA MASYARAKAT: STUDI KASUS ISLAM SEBAGAI TERAS IDENTITAS MELAYU DI MALAYSIA DENGAN METODE KAJIAN PUSTAKA - Yasin Muhammad Syibli; Aslan Aslan (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study examines the role of religion in shaping the identity and culture of a society, with a case study focusing on Islam as the core of Malay identity in Malaysia. Through a literature review, the study aims to analyse how Islam functions not only as a religion, but also as a constitutional, cultural and social foundation that binds Malay identity. This study examines the Malay constitutional definition that integrates Islam as a key element, as well as the influence of Islam on the customs, language, arts, and traditional practices of the Malay community. The results show that Islam plays a central role in shaping the social, cultural, and political norms of the Malay community, making Malay-Islamic identity a dynamic social construct that is resistant to the challenges of globalisation and modernisation. These findings reinforce the understanding that religion is a fundamental force in the formation of identity and preservation of Malay culture in Malaysia.